Early-onset versus late-onset fetal cerebral ventriculomegaly: Sonographic characteristics and neonatal outcomes - Dayanan, Ruken; Filiz, Ahmet Arif; Ayas Özkan, Merve; Duygulu Bulan, Dilara; Ayhan, Hatice; Bakan, Ecem; Karabay, Gülşan; Çelen, Şevki (The European Research Journal, 2025)
Objectives: This study aimed to compare the prenatal ultrasound characteristics, pregnancy outcomes, and neonatal prognosis of early- and late-onset fetal ventriculomegaly (VM). Methods: A retrospective analysis was conducted on 102 pregnant women diagnosed with fetal VM, categorized into early-onset (≤24 weeks) and late-onset (>24 weeks) groups. Maternal characteristics, ventricular dimensions, associated anomalies, pregnancy outcomes, and neonatal parameters were compared between the groups. Results: Early-onset VM was significantly associated with progressive ventricular enlargement, bilateral involvement, and a higher prevalence of additional anomalies detected via ultrasonography (70.4% vs. 29.2%, P